Senolytics (DQ) Mitigates Radiation Ulcers by Removing Senescent Cells - Wang, Huilan; Wang, Ziwen; Huang, Yu; Zhou, Yue; Sheng, Xiaowu; Jiang, Qingzhi; Wang, Yawei; Luo, Peng; Luo, Min; Shi, Chunmeng (Frontiers in Oncology, 2020)
Radiation ulcer is a prevalent toxic effect in patients receiving radiation therapy. At present, there is still no effective treatment for radiation ulcer. Senescent cells accumulate after radiation exposure, which can induce cells and tissues dysfunction. Here we demonstrated senescence biomarkers (p16 expression) accumulated in human radiation ulcer after radiotherapy and radiation induced persist cell senescence in animal ulcer models. Further, senescent cells secreted senescence-associated secretory phenotype (SASP) and induced cell senescence in adjacent cells, and JAK inhibition could alleviate SASP in senescent cells. In addition, the clearance of senescent cells by treatment with a senolytics cocktail, Dasatinib plus Quercetin (DQ), mitigated radiation ulcer. Finally, DQ induced tumor cell apoptosis and enhanced radio-sensitivity in representative CAL-27 and MCF-7 cell lines. Our study demonstrates that cell senescence are involved in the development of radiation ulcer and elimination of senescent cells might be a viable strategy to alleviate radiation ulcer.